2022
DOI: 10.1007/s40710-022-00603-w
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations and Effect of COVID-19 Lockdown Restrictions on the Air Quality in the Cities of Kazakhstan

Abstract: The objective of this study was to investigate the impact of COVID-19 lockdown on different air pollutants in eight cities of Kazakhstan by employing the data from the National Air Quality Monitoring Network. We selected eight cities located in different regions of the country with varied climatic and geographic conditions and emissions sources, providing good conditions for studying the differences in responses of air quality to COVID-19. Due to severe winters, the heating season in Kazakhstan has a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The research in [26] is devoted to the study of various air pollutants in eight cities of Kazakhstan during the quarantine period due to COVID-19, using data from the National Air Quality Monitoring Network. A positive effect of the COVID-19 quarantine (spring 2020) on NO 2 and CO levels was observed in five and three cities, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The research in [26] is devoted to the study of various air pollutants in eight cities of Kazakhstan during the quarantine period due to COVID-19, using data from the National Air Quality Monitoring Network. A positive effect of the COVID-19 quarantine (spring 2020) on NO 2 and CO levels was observed in five and three cities, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [26] claim that according to the results of the studied industrial cities (Ust-Kamenogorsk and Karaganda), quarantine measures had no effect on air quality, but seasonal changes were significant. In addition, despite some improvements during the quarantine period, air quality in seven of the eight cities remained below the safety level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Confinement by COVID-19 revealed different direct or indirect impacts on the environment and especially on-air quality (Zambrano-Monserrate et al 2020 ; Kumar et al 2020 ). Recent research has shown the positive impacts of confinement on air quality in cities around the world (Gopikrishnan et al 2022 ; Baimatova et al 2022 ; Balamurugan et al 2022 ; Ju et al 2021 ; Allu et al 2021 ; Lokhandwala and Gautam 2020 ; Arora et al 2020 ; Zangari et al 2020 ; Bera et al 2020 ; Selvam et al 2020 ; Zambrano-Monserrate and Ruano 2020 ; Archer 2020; Nakada and Urban 2020 ; Jain and Sharma 2020 ).…”
Section: Introductionmentioning
confidence: 99%